2009
DOI: 10.1111/j.1365-2265.2009.03589.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of gamma knife radiosurgery in acromegaly: a 10‐year follow‐up study

Abstract: Over a 10-year period after GK radiosurgery, an increasing percentage of patients achieve cure, or adequate control of the disease on pharmacological therapy, at the expense of increasing novel pituitary deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 33 publications
5
58
0
Order By: Relevance
“…By combining the high radiation precision known from SRS and the radiobiological advantages of fractionated radiation, FSRT is preferred over SRS when the target is close to a critical structure as, for example, the optic pathway (13,32). Also, FSRT is performed mostly using a dental or head mask, thereby avoiding the invasive pins used during SRS (the Cyberknife is an exception) (6).…”
Section: Authorsmentioning
confidence: 99%
“…By combining the high radiation precision known from SRS and the radiobiological advantages of fractionated radiation, FSRT is preferred over SRS when the target is close to a critical structure as, for example, the optic pathway (13,32). Also, FSRT is performed mostly using a dental or head mask, thereby avoiding the invasive pins used during SRS (the Cyberknife is an exception) (6).…”
Section: Authorsmentioning
confidence: 99%
“…For example, a 2009 study of GKS by Ronchi et al 85 found a 10-year time to remission, which is significantly slower than the times to remission reported with other series (Table 2). But these results reflect the fact that Ronchi et al reported remission rates in patients who were off somatostatin analog therapy at the time of radiosurgery using a strict 3 criteria must be met definition of remission (normal oral glucose tolerance test, "safe" GH levels, and normal IGF-I level), whereas other studies with faster times to remission included patients on medical therapy at the time of treatment and used only 1 or 2 criteria for remission.…”
mentioning
confidence: 53%
“…81 Another group found that initial GH and IGF-I levels while off somatostatin analogs were significantly higher in patients who did not achieve remission than in patients with biochemical remission, 13 which suggests that, even if being off antiacromegaly medications at the time of radiosurgery does not improve the chances of remission, another benefit of being off medications at the time of GKS is that the pretreatment hormone levels provide a better understanding of the likelihood of achieving remission with radiosurgery. 85 A study of 42 patients with endocrine active adenomas identified 2 other factors predicting remission in a multivariate analysis, higher total integral dose (p = 0.005), and maximum dosage (p = 0.001). 19 The integral dose represents the total energy absorbed by the adenoma during radiosurgery in gram rad units (1 g rad unit represents 100 ergs/g), while the maximum dosage represents the highest dose any part of the adenoma receives in Gray units.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…57,59 Radiosurgery is generally considered if the tumor is a minimal distance from the optic chiasm resulting in an exposure of more than 800 cGy. 60 Periodic withdrawal of medical therapy following radiotherapy should be performed for biochemical assessment. 6 SRLs are often withheld at the time of radiation therapy because of concern that they may be radioprotective, although this finding is controversial, as it is not supported in all studies.…”
Section: Radiation Therapymentioning
confidence: 99%